2007
DOI: 10.1007/s10570-007-9181-5
|View full text |Cite
|
Sign up to set email alerts
|

The implication of chemical extraction treatments on the cell wall nanostructure of softwood

Abstract: Spruce wood was subjected to welldefined extraction treatments with sodium chlorite (NaClO 2 ) for delignification, as well as with sodium hydroxide (NaOH) at different concentrations for extraction of hemicelluloses. The corresponding changes of the macromolecular polymer assembly were investigated by small-angle X-ray scattering (SAXS). Measurements with Fourier-transform infrared (FTIR) spectroscopy and wide-angle scattering (WAXS) gave qualitative information about the effectiveness of the extraction proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 51 publications
3
50
0
Order By: Relevance
“…Cracking of the wood cell wall during drying is a known process that has been reported in literature. 48,49 It was also shown that the MAA functionalization effectively reduced the shrinkages of the final materials by 64% (Dl rad in MA 2clc) in relation to the delig templates and increased the final masses of the 2inf samples by 213%, a phenomenon that was also reported by others. 43,50 The thermal properties of 2inf templates, assessed by simultaneous TGA/DTA analysis showed the mass losses and according DTA signals typical for cellulosic materials (Fig.…”
Section: A Dimensional and Mass Changessupporting
confidence: 71%
See 1 more Smart Citation
“…Cracking of the wood cell wall during drying is a known process that has been reported in literature. 48,49 It was also shown that the MAA functionalization effectively reduced the shrinkages of the final materials by 64% (Dl rad in MA 2clc) in relation to the delig templates and increased the final masses of the 2inf samples by 213%, a phenomenon that was also reported by others. 43,50 The thermal properties of 2inf templates, assessed by simultaneous TGA/DTA analysis showed the mass losses and according DTA signals typical for cellulosic materials (Fig.…”
Section: A Dimensional and Mass Changessupporting
confidence: 71%
“…Therefore, the scattering was presumably dominated by the contrast between the biopolymers and cracks that might have been formed upon drying the samples. 48 Infiltration of extracted templates with TEOS (extr inf and extr 2inf) did not change the scattering pattern significantly, suggesting that TEOS hardly penetrates into the cell wall. In the scattering patterns of the calcined samples (extr clc and extr 2clc), the fibrillar structures with radius 5 nm had completely disappeared.…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 92%
“…Jakob, et al (23) succeeded in extracting an interference contribution numerically, but it was small and difficult to characterize. From this observation it may be concluded that either the packing of wood microfibrils is too irregular to diffract strongly (42) or there is insufficient X-ray contrast between the microfibrils and any interstitial material (23). Intriguingly, an equatorial X-ray diffraction peak like that from celery cellulose microfibrils was observed after spruce wood was vigorously oxidized by chlorite/acetic acid (42).…”
Section: Resultsmentioning
confidence: 97%
“…As shown in the spectrum of sample D, after the delignification treatment, the bands at 1597, 1507, and 1459 cm -1 , corresponding to the aromatic skeletal vibration and other lignin related bands (e.g. 1648, 1324 cm -1 ), disappeared (Jungnikl et al 2008). It is evident that there was little to no remaining lignin in sample D, i.e., the lignin in the wood cell wall had been removed by the NaClO2/acetic acid.…”
Section: Main Chemical Componentsmentioning
confidence: 90%